Profitability of Islamic Microfinance in Indonesia: Does the Type of Financing Matter? - Chitra Yuliashri Katili; Rifadli D. Kadir (Department of Islamic Banking, 2021)
This study aims to examine the effect of Inflation Variables, CAR, NPF, Murabahah Financing, Mudharabah Financing, and Musyarakah Financing on the Profitability of Sharia BPRs in Indonesia. This study uses time series data from 2016-2020. The data is processed using the Error Correction Model (ECM). This study concludes that Murabahah Financing Variables have a significant influence and other variables, namely Inflation, CAR, NPF, Mudharabah Financing and Musyarakah Financing have no effect on the Profitability of Sharia BPRs in Indonesia. Thus, the type of financing affects the profitability of Sharia BPR in Indonesia